2014
DOI: 10.1038/modpathol.2013.147
|View full text |Cite
|
Sign up to set email alerts
|

The value of mutational profiling of the cytocentrifugation supernatant fluid from fine-needle aspiration of pancreatic solid mass lesions

Abstract: Fine-needle aspiration (FNA) of pancreatic solid masses can be significantly impacted by sampling variation. Molecular analysis of tumor DNA can be an aid for more definitive diagnosis. The aim of this study was to evaluate how molecular analysis of the cell-free cytocentrifugation supernatant DNA can help reduce sampling variability and increase diagnostic yield. Twenty-three FNA smears from pancreatic solid masses were performed. Remaining aspirates were rinsed for preparation of cytocentrifuged slides or ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…One possibility for this discrepancy lies in the nature of the neoplastic cell population. It is conceivable that some tumors may have a higher cellular turnover (i.e., increased mitosis, apoptosis, and necrosis), resulting in the shedding of DNA (cell-free DNA)[18222324] in the interstitial fluid of the tumor, which is then caught only in the supernatant. Therefore, the lack of BRAF mutations in the cellular component of these samples could be likely due to sampling issues (i.e., cancer cells with BRAF mutations were missed by the FNA needle in the fourth pass, which is the sample submitted to the reference laboratory, resulting in a negative cellular DNA analysis while the tumor cells with the BRAF mutations were obtained from the first three FNA passes and therefore were present in the supernatant fluid leading to a positive supernatant DNA analysis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility for this discrepancy lies in the nature of the neoplastic cell population. It is conceivable that some tumors may have a higher cellular turnover (i.e., increased mitosis, apoptosis, and necrosis), resulting in the shedding of DNA (cell-free DNA)[18222324] in the interstitial fluid of the tumor, which is then caught only in the supernatant. Therefore, the lack of BRAF mutations in the cellular component of these samples could be likely due to sampling issues (i.e., cancer cells with BRAF mutations were missed by the FNA needle in the fourth pass, which is the sample submitted to the reference laboratory, resulting in a negative cellular DNA analysis while the tumor cells with the BRAF mutations were obtained from the first three FNA passes and therefore were present in the supernatant fluid leading to a positive supernatant DNA analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of detecting BRAF mutations in FNA supernatants of PTC are in agreement with the results of a recent study, which demonstrated that the use of FNA supernatant specimens from patients with pancreatic cancers for molecular testing may outperform cellular DNA analysis in certain situations. [18] We attempted to quantify the DNA amounts in the supernatant; however, the majority of samples showed the amount of DNA was below the linear range of NanoDrop 1000 (Thermo Scientific, Wilmington, DE) even though 87% of our samples had enough amplifiable DNA for the detection of BRAF mutation. Of note, we only used 200 µl of about 25–50 ml supernatant for DNA extraction; therefore the yield of DNA could potentially be increased if a greater amount of supernatant was used for DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically for the ThinPrep slide, a small aliquot of pelleted material is transferred into the standard PreservCyt fixative jar (Hologic) per manufacturer's protocol and processed accordingly. Based on a recent study showing a substantial amount of nucleic acid in the supernatants of FNA needle rinses after cell pelleting, 25 we have modified our process to preserve the CytoLyt supernatants, material that has traditionally been discarded in the majority of cytopathology laboratories, for molecular studies. In addition, any unused cell suspension from the PreservCyt container is also saved.…”
Section: Redefining Cytology Sample Processing Formentioning
confidence: 99%
“…12 Postcentrifuged supernatant fluid from FNA needle rinses has been known to yield substantial amounts of DNA that are sufficient for assays such as microsatellite fragment analysis for loss of heterozygosity as well as hotspot-based mutational analysis by PCR/capillary electrophoresis and pyrosequencing. [13][14][15][16][17] A recent study by our group demonstrated that supernatant fluid samples from FNA needle rinses can provide adequate DNA for NGS and droplet digital PCR to provide clinically relevant genomic information for a variety of solid tumors, including lung carcinoma, melanoma, and colorectal adenocarcinoma. 18 Furthermore, another recent study has demonstrated the feasibility of using supernatant DNA fluid from patients with lung cancer for tumor genotyping by mutational analysis.…”
mentioning
confidence: 99%